Analysis of the Effect of Social Media Marketing on MSME Performance at Citra Cosmetic Makassar - Monica Sari Kumala; Rosdiana Sijabat (Kontigensi : Jurnal Ilmiah Manajemen, 2022)
The aims of the research on the Effect of Social Media Marketing on Micro Enterprises in Indonesia are: 1) To find out the positive influence of Customer Engagement on the performance of MSME Citra Cosmetic Makassar, 2) To find out the positive influence of Customer Satisfaction on MSME performance through Customer Loyalty. Citra Cosmetic Makassar, 3) To find out the positive influence of Customer Brand Reputation on the performance of MSME Citra Cosmetic Makassar, 4) To find out the positive influence of Customer Loyalty on the performance of MSME Citra Cosmetic Makassar. The data collection was based on people who live in Makassar and ever made a purchase on Citra Cosmetic Makassar. By doing this research, it has a purpose and can also contribute to the owners of Citra Cosmetic Makassar in order to increase their own QMS. The results of the discussion used a program from PLS to analyze data and also surveys. The sampling technique of this research is to use non-probability sampling with purposive sampling method, the data collection method used itself is to use a survey of 385 samples and also use the outer model and inner model tests. The results of this study themselves prove that three of the four hypotheses are accepted.